Gray zone: a case report on borderline mucinous tumor - S., Srinidhi; Palaniappan, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Borderline ovarian tumors (BOTs) represent an intermediate form between benign and malignant epithelial ovarian neoplasms, with mucinous subtype accounting for a significant proportion. These tumors often present in women of reproductive age and are frequently diagnosed at an early stage. We report the case of a 25-year-old unmarried woman with regular menstrual cycles who was incidentally found to have a complex left adnexal mass during routine imaging. Clinical examination revealed a firm, midline abdominopelvic mass corresponding to 20 weeks’ uterine size. Tumor markers, including CA-125, CEA, CA 19-9, AFP, and LDH, were within normal limits. MRI pelvis revealed a 15 cm mixed solid-cystic lesion in the left adnexa. Intraoperatively, a unilateral ovarian mass with no evidence of extraovarian spread was noted. Frozen section was suggestive of a borderline mucinous tumor. The patient underwent a fertility-sparing staging laparotomy including left salpingo-oophorectomy, infracolic omentectomy, appendicectomy, pelvic lymph node dissection, and peritoneal biopsies. Final histopathology confirmed a borderline mucinous tumor, FIGO Stage IA. This case highlights the importance of thorough preoperative evaluation and intraoperative decision-making in young women with adnexal masses. Fertility-sparing surgery with complete staging offers an excellent prognosis in early-stage borderline mucinous ovarian tumors, with the added benefit of preserving reproductive potential.